2019
DOI: 10.1016/j.dcm.2019.03.001
|View full text |Cite
|
Sign up to set email alerts
|

From transliteration to trans-scripting: Creativity and multilingual writing on the internet

Abstract: Although research on multilingual writing has widely explored transliteration and, particularly, Romanization practices, we know little about how related phenomena are reconfigured in social media contexts where users can manipulate a wide range of writing resources and navigate between multiple intertwining audiences. By analysing more than one thousand tokens of forms that illustrate what appears as reversed Romanization (i.e. Englishrelated forms written with Greek characters, engreek), the study aims to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
0
13
0
6
Order By: Relevance
“…In this study, I refer specifically to cases where English‐related forms are spelled with non‐Roman characters, following a writing system that is normally associated with another language (trans‐scripting; Androutsopoulos, ; Spilioti, ). What is distinctive of the relocalization of such English‐related forms as words written in the local alphabet is the fact that their transformation makes them less mobile in a global world; they are recognizable only by the local multilingual audiences and probably meaningless to a range of speakers who would claim competence in the English language.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, I refer specifically to cases where English‐related forms are spelled with non‐Roman characters, following a writing system that is normally associated with another language (trans‐scripting; Androutsopoulos, ; Spilioti, ). What is distinctive of the relocalization of such English‐related forms as words written in the local alphabet is the fact that their transformation makes them less mobile in a global world; they are recognizable only by the local multilingual audiences and probably meaningless to a range of speakers who would claim competence in the English language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The current study is part of a wider project that focuses on multilingual phenomena in digital communication and undertakes a multi‐sited approach for the study of respellings of English‐related forms with Greek characters (Spilioti, ). During the four‐year research journey, I have observed, followed, and documented ‘engreek’ uses across multiple media and platforms, including YouTube, Facebook, online dictionaries, webpages, social media marketing campaigns, and popular memes.…”
Section: Research Context and Designmentioning
confidence: 99%
“…including letters such as š and č) versus using some kind of English approximation for Latin. They could bring together these choices in unconventional mixtures, such as using Cyrillic or Latin to represent English words or phrases (what Spiloti (2019), writing about Greek, has termed trans-scripting ) or borrowing from English spelling rules to create a visually distinct form of Serbian.
Figure 2.Uses of Serbian and English/Cyrillic and Latin on Facebook.
…”
Section: Brief Historical Background and Current Language Situationmentioning
confidence: 99%
“…Πιο συγκεκριμένα, τα Greeklish, σύμφωνα με ορισμένους μελετητές, συνιστούν στοιχείο της διαλεκτικής και διαπραγματεύσιμης σχέσης ανάμεσα στο παγκόσμιο και το τοπικό, της μετακίνησης των πόρων και της ρευστότητας που χαρακτηρίζει την έξω από τις παραδοσιακές νόρμες γλωσσική δραστηριότητα των χρηστών/τριών του διαδικτύου (Androutsopoulos 2015, Spilioti 2019). Στο πλαίσιο αυτό, μια νέα μετανεωτερική ταυτότητα διαμορφώνεται και αντιτάσσει στα κανονιστικά ορθογραφικά πρότυπα της εθνικής ταυτότητας νέες υβριδικές πρακτικές γραφής.…”
Section: πλαίσιο προβληματισμούunclassified
“…This system, which bears the mark of globalization, deviates from the national writing standards in digital media (cf. Androutsopoulos 2015, Spilioti 2019 and is connected with a new type of literacy, which challenges both the standards of the Modern Greek cultural literacy and those of the archaistic cultural literacy.…”
Section: Introductionmentioning
confidence: 99%